Lipidomics profiling of zebrafish liver through untargeted liquid chromatography‐high resolution mass spectrometry. Issue 15 (3rd July 2022) - da Silva, Katyeny Manuela; Iturrospe, Elias; van den Boom, Rik; van de Lavoir, Maria; Robeyns, Rani; Vergauwen, Lucia; Knapen, Dries; Cuykx, Matthias; Covaci, Adrian; van Nuijs, Alexander L. N.
Abstract : Lipidomics analysis of zebrafish tissues has shown promising results to understand disease‐related outcomes of exposure to toxic substances at a molecular level. However, knowledge about their lipidome is limited, as most untargeted studies only identify the lipids that are statistically significant in their setup. In this work, liquid chromatography‐high resolution mass spectrometry was used to study different aspects of the analytical workflow, that is, extraction solvents (methanol/chloroform/water (3/2/2, v/v/v), methanol/dichloromethane/water (2/3/2, v/v/v) and methanol/methyl‐tert‐butyl ether/water (3/10/2.5, v/v/v), instrumental response, and strategies used for lipid annotation. The number of high‐quality features (relative standard deviation of the intensity values ≤ 10% in the range 10 3 −10 7 counts) was affected by the dilution of lipid extracts, indicating that it is an important parameter for developing untargeted methods. The workflows used allowed the selection of a dilution factor to annotate 712 lipid species (507 bulk lipids) in zebrafish liver using four software (LipidMatch, LipidHunter, MS‐DIAL, and Lipostar). Retention time mapping was a valuable tool to filter lipid annotations obtained from automatic software annotations. The lipid profiling of zebrafish livers will help in a better understanding of the true constitution of their lipidome at the species level, as well as in the use of zebrafish in toxicological studies.